The Doll's House and Other Stories: level 4 - Mansfield K. Katherine (Penguin Readers)
Katherine Mansfield wrote some of the best short stories in the English language. These four stories take place in England and New Zealand. They are funny, sad and often cruel. A collection of short stories by one of the most outstanding female writers of this century.